Line parameters for CO2- and self-broadening in the ν1 band of HD16O. (December 2017) - Devi, V. Malathy; Benner, D. Chris; Sung, Keeyoon; Crawford, Timothy J.; Gamache, Robert R.; Renaud, Candice L.; Smith, Mary Ann H.; Mantz, Arlan W.; Villanueva, Geronimo L.
Abstract: Lorentz half-width coefficients and their temperature dependence exponents for CO2 broadening in the fundamental bands of HDO are important for reliable and accurate interpretation of Mars and Venus atmospheric data and to determine D/H. Uncertainties in the temperature dependences of the CO2 -broadened half-width coefficients lead to large errors in the retrieved mixing ratios and hence in HDO column abundances. In this high-resolution FTIR laboratory study, we report first measurements of the temperature dependences of half-width coefficients for HDO transitions in the ν1 and 2ν2 bands broadened by CO2 . Accurate line positions, intensities, CO2 -broadened width and pressure shift coefficients, their temperature dependences, collisional line mixing coefficients for HDO-CO2 system and quadratic speed dependence parameters have been retrieved for a large number of transitions in the ν1 band. Room-temperature self-broadened half-width coefficients, self-shift coefficients, and collisional line-mixing coefficients for HDO-HDO system were also measured for the same number of ν1 transitions. Positions and intensities were measured for nearly 60 transitions in the weaker 2ν2 band along with a few room-temperature measurements of CO2 - and self-broadening and pressure-shift coefficients. These results were obtained from simultaneous nonlinear least squares fittings of ten high-resolution absorption spectra recorded with the Bruker IFS-125HR FTS at JPL and two coolable sample cells. Modified Complex Robert-Bonamy (MCRB) formalism was applied to compute both types of broadening and pressure shift coefficients, and the temperature dependences of the CO2 - and self-broadening parameters. Present measurements are compared with the MCRB calculations and other theoretical values reported in the literature. Highlights: Positions and intensities for over 200 transitions in the ν1 and 2ν2 bands of HDO. Measured CO2 - and self-broadened widths and shifts for 150 lines in the ν1 and 2ν2 . Calculated MCRB line shape parameters for HDO transitions in the ν1 and 2ν2 bands. Temperature dependences of HDO-CO2 widths and shifts for 90 transitions in the ν1 . Speed dependence and relaxation matrix element coefficients in the ν1 band of HDO.